Legal Protection for Children Who Experience Psychological, Emotional, and Moral Abuse in Society - Setyawati, ‎ (KnE Social Sciences, 2025)
This research examines the framework of legal protection for children who are victims of psychological, emotional, and moral abuse in society. While physical and sexual abuse often receive the most public and legal attention, these non-physical forms of abuse have damaging and often invisible impacts that can fundamentally hinder a child’s development. This study analyzes existing legal instruments, both international and national, to identify the extent of available legal protection and the challenges in its enforcement. Theoretically, legal protection against non-physical abuse of children is rooted in the principles of child human rights, recognized in the UN Convention on the Rights of the Child (CRC) and child protection laws in many countries. However, this research finds that legal implementation on the ground faces several significant challenges. These challenges include: 1) Lack of clear definitions: Psychological, emotional, and moral abuse are often difficult to define legally, making them challenging to prove in court. 2) Invisible nature: Non-physical forms of abuse leave no physical marks, which complicates evidence gathering and often leads to cases not being taken seriously. 3) Challenges in proving cases: The subjective nature of non-physical abuse makes proof complex, as it often relies on the testimony of a vulnerable child or indirect evidence. 4) Lack of awareness: There is a lack of awareness among the public, law enforcement officials, and even parents about the dangers of non-physical abuse to children. This study concludes that effective legal protection for children who are victims of non-physical abuse requires a multidisciplinary approach. It is crucial to enact legal reforms to provide clearer definitions and stronger sanctions, enhance training for law enforcement officials, and build robust psychological and social support systems for children. Additionally, public awareness campaigns are needed to change perceptions and encourage society to be more sensitive to these hidden forms of abuse, ensuring every child can grow up in a safe and supportive environment.